Does millet consumption contribute to raising blood hemoglobin levels compared to regular refined staples?: a systematic review and meta-analysis - Anitha, Seetha; Tsusaka, Takuji W.; Givens, D. Ian; Kane-Potaka, Joanna; Botha, Rosemary; Sulaiman, Nur Liana Binti; Upadhyay, Shweta; Vetriventhan, Mani; Rajendran, Ananthan; Parasannanavar, Devraj J.; Longvah, Thingnganing; Subramaniam, Kowsalya; et al. (Frontiers in Nutrition, 2024)
Millets are recognized for their health and nutritional values and the United Nations declared 2023, the International Year of Millets. Among several health and nutritional benefits of millets, their impact on hemoglobin concentration is important since anemia is a major public health issue in many countries. To investigate the effects of the the consumption of millets (including sorghum) consumption on hemoglobin concentration in of blood, a systematic review and a meta-analysis were conducted. ofwith Thirteen 13 published studies featuring randomized controlled trials involving 590 individuals in intervention group treated individuals and 549 controlled individuals were eligible for the meta-analysis. The difference-in-differences analysis revealed highly significant (p < 0.01) positive effects of millet consumption on hemoglobin levelsconcentration, with an effect size of +0.68 in the standardized mean difference units. The percentage change in hemoglobin levelsconcentration observed in the intervention group was +13.6% which is statistically significant (p < 0.0005), while thecompared to that in change the control group which was +4.8% and not statistically significant (p = 0.1362) in the control group. In four studies, consumption of millets in the intervention group demonstrated a change from mild anemia to normal status among children, whereas there was no change in the control group. The findings result provides evidence that the consumption of millets can helps improve blood hemoglobin concentration, likely resulting from increased iron intake. Further research is needed involving the assessment of iron content and bioavailability to better understand the effect variation amongst millet types and the mechanisms involved. .